A Critical Scrutiny on Liposomal Nanoparticles Drug Carriers as Modelled by Topotecan Encapsulation and Release in Treating Cancer. (9th August 2022) - Mills, Hilla; Acquah, Ronald; Tang, Nova; Cheung, Luke; Klenk, Susanne; Glassen, Ronald; Pirson, Magali; Albert, Alain; Hoang, Duong Trinh; Van, Thang Nguyen
Abstract : The medical field is looking for drugs and/or ways of delivering drugs without harming patients. A number of severe drug side effects are reported, such as acute kidney injury (AKI), hepatotoxicity, skin rash, and so on. Nanomedicine has come to the rescue. Liposomal nanoparticles have shown great potential in loading drugs, and delivering drugs to specific targeted sites, hence achieving a needed bioavailability and steady state concentration, which is achieved by a controlled drug release ability by the nanoparticles. The liposomal nanoparticles can be conjugated to cancer receptor tags that give the anticancer-loaded nanoparticles specificity to deliver anticancer agents only at cancerous sites, hence circumventing destruction of normal cells. Also, the particles are biocompatible. The drugs are shielded by attack from the liver and other cytochrome P450 enzymes before reaching the desired sites. The challenge, however, is that the drug release is slow by these nanoparticles on their own. Scientists then came up with several ways to enhance drug release. Magnetic fields, UV light, infrared light, and so on are amongst the enhancers used by scientists to potentiate drug release from nanoparticles. In this paper, synthesis of liposomal nanoparticle formulations (liposomal-quantum dots (L-QDs), liposomal-quantum dots loaded with topotecan (L-QD-TPT)) and their analysis (cytotoxicity, drug internalization, loading efficiency, drug release rate, and the uptake of the drug and nanoparticles by the HeLa cells) are discussed.